HOSPITALITY: A PLACE OF MEETING WITH THE BIOETHICS WHIT GASTRONOMY - Oliveira, Celso Ramos de; Butuhy, Cláudia Regina Rodrigues Sarralheiro; Butuhy, Júlio César; Inojosa, Pedro Campana (Tourism & Management Studies, 2013)
Bioethics presents itself as a great call for the different areas of knowledge and human activities that deepen on ethical issues that are relevant. This reflection offers some initial steps to understand and challenge of bioethical reflection in Gastronomy. After a brief setting of the concepts in view of the delimitation subject, explains to hospitality as a summary of the meeting place of the Gastronomy in Bioethics. It generates not only proposals for warmth and respect in food services, but also appear critical remarks about the current cultural moment is not always conducive to the unfolding of the attitudes of hospitality. Sketches in this way a brief outline of reading Bioethics in Gastronomy, with in the current context, little literature on this subject.